Four Ways Life Extension will Change Our Relationship with Death. (23rd April 2015) - Davis, John K.
Abstract: Discussions of life extension ethics have focused mainly on whether an extended life would be desirable to have, and on the social consequences of widely available life extension. I want to explore a different range of issues: four ways in which the advent of life extension will change our relationship with death, not only for those who live extended lives, but also for those who cannot or choose not to. Although I believe that, on balance, the reasons in favor of developing life extension outweigh the reasons against doing so (something I won't argue for here), most of these changes probably count as reasons against doing so. First, the advent of life extension will alter the human condition for those who live extended lives, and not merely by postponing death. Second, it will make death worse for those who lack access to life extension, even if those people live just as long as they do now. Third, for those who have access to life extension but prefer to live a normal lifespan because they think that has advantages, the advent of life extension will somewhat reduce some of those advantages, even if they never use life extension. Fourth, refusing life extension turns out to be a form of suicide, and this will force those who have access to life extension but turn it down to choose between an extended life they don't want and a form of suicide they may (probably mistakenly) consider immoral.